MAGUEREZ ARCH AS A HEALTH EDUCATION PEDAGOGICAL METHODOLOGY FOR HEALTH EDUCATION ON AUTISM. - Nepomuceno, Samara; Paiva, Jocilene; Bernardo, Francisco; Ferreira, Diego; Soares, Ana; Rouberte, Emília; Oliveira, Paula; Pinto, Cristina; Cantante, Ana; MotA, Liliana (RIIS: Revista de Investigação & Inovação em Saúde, 2025)
Background: the Maguerez Arc stands out as an active teaching methodology that stimulates the problematization of reality and the critical-reflective construction of knowledge, being widely used in the health field, including education about Autism Spectrum Disorder (ASD). Objective: to describe experiences resulting from the use of the Maguerez Arc as a pedagogical strategy in health education about ASD. Methodology: a qualitative study, experience report type, developed by researchers in a philanthropic association in the city of Porto, in February 2025. The activity followed the five stages of the Maguerez Arc and was aimed at parents who were waiting to receive food baskets (n=12). Results: the methodology proved effective in promoting active participation and the collective construction of knowledge about ASD. Observations indicated an evolution in initial perceptions, reflecting significant learning in understanding the characteristics of autism, recognition of the importance of inclusion, and interest in disseminating this information. Conclusion: this strategy proved promising for linking theoretical knowledge with community practice, fostering critical reflection and strengthening health literacy. Future studies could explore this approach in different contexts, evaluating its impact on promoting inclusion and supporting families of children with ASD.